Lichen Sclerosus or Vulvar Angiokeratoma: A Diagnosis That Is Not Always So Easy - De Giorgi, Vincenzo; Perillo, Gabriella; Antonini, Pietro; Cecchi, Giovanni; Zuccaro, Biancamaria; Magnaterra, Elisabetta; Castellacci, Eleonora; Massi, Daniela (Dermatology Practical & Conceptual, 2025)
–